Vegetation patterns along agricultural land abandonment in the Balkans. (13th August 2018) - Zakkak, Sylvia; Radovic, Andeja; Panitsa, Maria; Vassilev, Kiril; Shuka, Lulëzim; Kuttner, Michael; Schindler, Stefan; Kati, Vassiliki
Abstract: Question: What are the woody vegetation encroachment patterns after agricultural land abandonment? Focusing on two parameters, woody plant species richness and vertical vegetation heterogeneity (number of different vegetation strata and their relative cover) we investigated: (a) the effect of forest encroachment following land abandonment; (b) the comparative importance of forest encroachment vis‐a‐vis topographic and climatic parameters, and finally; (c) the ecological importance of eight land‐cover types encountered in abandoned agricultural landscapes. Location: The Balkan Peninsula (Albania, Bulgaria, Croatia, Greece). Methods: We set up a standard methodology for 1 × 1 km site selection (70 sites) and data collection within 497 plots, along a well‐defined forest encroachment gradient that reflects land abandonment in terms of woody vegetation cover. Results: The pattern that emerged was neither clear nor common for the Balkan region, regarding the effect of forest encroachment on the woody plant species richness in young forests, formed from 20 to 50 years after land abandonment. However, at national level, species diversity was significantly affected by elevation (Bulgaria and Croatia) and temperature (Croatia), with lower and cooler areas being richer. Elevation was of great importance in determining vertical vegetation heterogeneity. Woodlots, broad‐leaved forests, hedges and shrublands held the highest woody species richness in comparison to the more open land‐cover types, and vertical vegetation heterogeneity was higher in open forests and woodlots. Conclusions: We expect the expansion of broad‐leaved forests following land abandonment to enhance woody species richness. However, other land‐cover types that were found to be important for woody plants should be maintained. As woody plants play a key role in supporting overall biodiversity, by providing suitable habitat for many species, we consider the preservation of a mosaic of patches of different land‐cover types essential for the conservation of both plant and animal species diversity. Young forests should be preserved at intermediate stages of succession, through intermediate disturbance activities, including medium intensity grazing and the enhancement of wild ungulates. Abstract : Forest encroachment following land abandonment had no significant effect on the woody plant species richness in the Balkans; elevation and temperature had a negative effect locally. Woodlots, broad‐leaved forests, hedges and shrublands held the highest woody species richness, and vertical vegetation heterogeneity was higher in open forests and woodlots. Different land‐cover types should be maintained, enhancing landscape heterogeneity.